Impact of vehicular traffic emissions on particulate-bound PAHs: Levels and associated health risks - Klara Slezakova (2013)
Considering vehicular transport as one of the most health-relevant emission sources of urban air, and with aim to further understand its negative impact on human health, the objective of this work was to study its influence on levels of particulate-bound PAHs and to evaluate associated health risks. The 16 PAHs considered by USEPA as priority pollutants, and dibenzo[a, I]pyrene associated with fine (PM2.5) and coarse (PM2.5-10) particles were determined. The samples were collected at one urban site, as well as at a reference place for comparison. The results showed that the air of the urban site was more seriously polluted than at the reference one, with total concentrations of 17 PAHs being 2240% and 640% higher for PM2.5 and PM2.5-10, respectively; vehicular traffic was the major emission source at the urban site. PAHs were predominantly associated with PM2.5 (83% to 94% of Sigma(PAHs) at urban and reference site, respectively) with 5 rings PAHs being the most abundant groups of compounds at both sites. The risks associated with exposure to particulate PAHs were evaluated using the TEF approach. The estimated value of lifetime lung cancer risks exceeded the health-based guideline levels, thus demonstrating that exposure to PM2.5-bound PAHs at levels found at urban site might cause potential health risks. Furthermore, the results showed that evaluation of benzo[a] pyrene (regarded as a marker of the genotoxic and carcinogenic PAHs) alone would probably underestimate the carcinogenic potential of the studied PAH mixtures.